Design and simulation of 5kW BLDC motor with half-buried permanent magnets using an existing stator body - Budi Azhari; Pudji Irasari; Puji Widiyanto (International Journal of Power Electronics and Drive Systems (IJPEDS), 2021)
This paper proposes a design of a 5 kW, 100 volts brushless direct current (BLDC) motor using an existing stator connected to an inverter and equipped with Hall sensors. The stator is a radial flux motor-type with 54 slots positioned at the outer side of the machine. In this case, the design is focused on the rotor components and winding configuration. However, the inverter aspects are also taken into account. At the same time, it considers the expected outputs: voltage, power, speed; and some limitations: maximum current and flux density. Finite element magnetic-based simulation is performed to extract the magnetic flux distribution, and analytical calculations are then conducted to obtain the output values and characteristics. The results show the BLDC motor at nominal speed produces 5.1 kW output power with 122.34 V voltages, 97.09% efficiency, and torque of 32.82 Nm. The maximum torque and rotation speeds are 51.39 Nm and 4,150 rpm respectively, while the peak-to-peak cogging force is 1.35 Nm. It can be concluded that the BLDC motor has a good performance and is compatible with the connected inverter.